2018
DOI: 10.5114/jcb.2018.75600
|View full text |Cite
|
Sign up to set email alerts
|

A single institution analysis of low-dose-rate brachytherapy: 5-year reported survival and late toxicity outcomes

Abstract: PurposeTo report the 5-year biochemical relapse-free survival (BRFS), overall survival (OS), and long-term toxicity outcomes of patients treated with low-dose-rate (LDR) brachytherapy as monotherapy for low- to intermediate-risk prostate cancer.Material and methodsBetween 2004 and 2011, 371 patients were treated with LDR brachytherapy as monotherapy. Of these, 102 patients (27%) underwent transurethral resection of the prostate (TURP) prior to implantation. Follow-up was performed every 3 months for 12 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…A prior mini TURP did not result in a urinary incontinence rate of 18% as previously reported by Kollmeier et al . The use of a prior mini TURP in LDR brachytherapy has also shown similar low GU toxicity with no urethral necrosis or urinary incontinence reported …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A prior mini TURP did not result in a urinary incontinence rate of 18% as previously reported by Kollmeier et al . The use of a prior mini TURP in LDR brachytherapy has also shown similar low GU toxicity with no urethral necrosis or urinary incontinence reported …”
Section: Discussionsupporting
confidence: 81%
“…19,20 A prior mini TURP did not result in a urinary incontinence rate of 18% as previously reported by Kollmeier et al 21 The use of a prior mini TURP in LDR brachytherapy has also shown similar low GU toxicity with no urethral necrosis or urinary incontinence reported. 22,23 The use of HS was also safe with all patients successfully implanted with no postoperative complications reported. In addition, we reported less GI rectal toxicities in patients who underwent HS insertion.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, the cumulative incidence of late grade 3 GU toxicity was 6.5%, consistent with most reports except the ASCENDE-RT study [10]. This is no different to the incidence of late grade 3 GU toxicity in LDR alone and this is widely considered to be acceptable [8,[13][14][15].…”
Section: Discussionsupporting
confidence: 90%
“…The NRG Oncology/RTOG0232 study [7] [8]. This cohort consisted of Gleason score 3þ4¼7 or ISUP group 2 prostate cancers with PSA <10 and clinical stage T1c-2a disease only.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapid dose fall off associated with brachytherapy, one can achieve an increased BED while limiting normal tissue toxicity. Both high-dose-rate (HDR) and low-dose-rate (LDR) techniques exist, each with a unique set of advantages and disadvantages [16,17,18]. In the definitive management of prostate cancer, brachytherapy can be used as a monotherapy or as a boost with EBRT depending on the aggressiveness of the disease, with favorable outcomes compared to EBRT alone [19,20].…”
Section: Purposementioning
confidence: 99%